(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
The aim of this study is to evaluate the effect of aerogel on Thermal Protective Performance (TPP) of fire fighter clothing. Specimens were treated by 5 wt% aerogel dispersed in acetone to obtain variousfi add-on of aerogel and their TPP were evaluated by flame heat transmission test according to ISO 9151. The thermal degradation behavior, flame retardancy and water vapor permeability of aerogel treated specimens were also examined. Finally, the comparison of the burn injuries predicted by instrumented manikin testing of aerogel treated fire fighter clothing and existing fire fighter clothing were performed. The result showed that aerogel treated fire fighter clothing exhibited higher TPP than the existing firefighter clothing. This suggests that there application of aerogel in fire fighter clothing may be possible.